What Is the Impact of Online Resource Materials on Student Self-Learning Strategies? - Dowell, David John; Small, Felicity A. (Journal of marketing education, 2011)
The purpose of this article is to examine how students are incorporating online resources into their self-regulated learning strategies. The process of developing these learning strategies and the importance of these strategies has been widely researched, but there has been little empirical research into how the students are affected by online environments. This preliminary study focused on the relationship between the use of online resources and the students’ overall outcome in the subject. The data were collected from first year on-campus (n = 105) and distance education (n = 258) students after completing their introductory marketing subject. The data were analyzed using correlations, simple regression, and Tobit regression to assess online activity and student outcomes. The results indicate that the use of these online resources has a significant and positive effect on the students’ grade. This finding suggests students are incorporating online environments into their learning strategies, which results in higher grades. Moreover, in practical terms, the results imply that teachers can help facilitate student self-learning strategies by creating encouraging and resource-rich online environments.